Recurrent parotitis. Issue 8 (August 1992) - Cohen, H A; Gross, S; Nussinovitch, M; Frydman, M; Varsano, I
Abstract : Recurrent parotitis in children is a well described but rare condition of unknown cause. The clinical features of 11 children with recurrent parotitis are described.